THE RELATIONSHIP BETWEEN HUSBAND'S KNOWLEDGE AND SUPPORT WITH FE TABLET CONSUMPTION COMPLIANCE IN PREGNANT WOMEN IN THE WORKING AREA OF CIREUNDEU PUSKESMAS IN 2022 - Alma Alfianti; Dewi Purnamawati; Nurfadhilah; Luqman Efendi (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
According to data from the Indonesian Ministry of Health, the prevalence of anemia or lack of blood in pregnant women in Indonesia in 2019 is still relatively high, namely 48.9%(1). Anemia in pregnant women can increase the risk of premature birth, antepartum bleeding, postpartum bleeding which causes death in mother and child and infectious diseases.(2) This study aims to determine the relationship of husband's knowledge and support with adherence to consumption of Fe tablets in pregnant women in the Working Area of ​​the Cireundeu Health Center. This study used quantitative analytic methods with a cross sectional study design and used a purposive sampling technique. The number of respondents was 46 pregnant women in the Working Area of ​​the Cireundeu Health Center. The data analysis in this study used the chi-square statistical test (α = 0.05) in the SPSS statistical software. Pregnant women who have good knowledge are 25 (54.3%). There were 28 (60.9%) pregnant women who received support from their husbands. There were 26 (56.5%) pregnant women who adhered to the consumption of Fe tablets. The variable associated with Fe Tablet Adherence in pregnant women in the Cireundeu Health Center Work Area was Husband's Support (P Value 0.025 OR = 5,000) The variable that was not related was Knowledge (P Value 0.413 OR = 1.956). Husband's support is related to adherence to consumption of Fe tablets while knowledge is not related to adherence to consumption of Fe tablets in pregnant women in the Working Area of ​​the Cireundeu Health Center. Suggestions for the health center namely monitor routinely the compliance of pregnant women in consuming Fe tablets and provide education to husbands as well as involving the education of husbands and pregnant women regarding the importance of Fe tablets during pregnancy so as to avoid iron deficiency anemia in pregnant women.